EFFECTS OF RHIZOBIA AND AZOTOBACTER ON YIELD AND YIELD COMPONENTS OF CHICKPEA (CICER ARIETINUM L.) - E. Takil; N. Kayan (Journal of Animal and Plant Sciences, 2023)
Biofertilizers have long been assessed as a powerful technology to obtain sustainable enhanced crop production. Azotobacter has been universally accepted as a major inoculum used in biofertilizers to restore the nitrogen level in a cultivated field. This study was carried out in dry farming areas in 2017 and 2019 to examine the effects of nitrogen application and different bacterial applications on the yield and yield components of chickpea cultivars. In the study, the effects on chickpea grain yield and yield components were evaluated by using two nitrogen doses (0 and 25 kg ha-1), four chickpea cultivars (Azkan, Akca, Cakir, Isik) and four bacteria applications (control, Rhizobia, Azotobacter, Rhizobia + Azotobacter). The experimental design was split split plot with three replicates. Nitrogen doses were in main plots, chickpea cultivars in subplots and bacteria application in sub-sub plots. All of the investigated characters except for hundred kernel weight and harvest index were higher during the first year than in the second year due to higher precipitation. All of the investigated characters increased with nitrogen application except for seed germination and hundred kernel weight. In terms of the examined cultivars, Azkan variety gave the highest values, followed by Akca variety. In general, co-inoculation of Rhizobia and Azotobacter enhanced all of the investigated characters except for seed germinations. Co-inoculation may be a technique essential for chickpea production but intensive further work is needed to develop this technology for commercial use by farmers.
Keywords: Azotobacter; nitrogen; rhizobia; yield components; yield